Filsafat Pengharapan dan Perwujudannya dalam Suasana Duka - Sermada Kelen Donatus (Sekolah Tinggi Widya Sasana, 2021)
Sorrows are universal human experiences hitting all human beings with different intensity. The article provides two concrete examples of sorrows, the first due to Covid-19 disaster and the latter due to stabbing case in Sigi, as an entrance to reflect philosophically on the essence of human hope. The opposite and the enemy of the human hope are despair and death. Genuine human hope should be constituted and realized in the midst of sorrowful experiences to cope with human despair and death. The last part of the article offers the way of realizing genuine human hope for the victims of calamities caused by natural disasters, diseases, or human malice. Love and compassion are the best response for the realization of the genuine human hope.